Immunodetection of Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH), Thyroid Stimulating Hormone (TSH) and Prolactin (PRL) in Brachionus calyciflorus (Rotifera: Monogononta) - Jesús Alvarado-Flores; María Del Rosario Montoya-Garcia; Javier Ventura Juárez; Roberto Rico-Martínez (Revista de Biología Tropical, 2009)
The endocrine system controls and coordinates behavioral, biochemical, and physiological processes through signal mechanisms using neuropeptides or products of neurosecretory cells. Among invertebrates, this system is poorly studied in rotifers, in which estrogens and androgens significantly affect sexual reproduction. This is the first report of the presence of the Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH), Thyroid Stimulating Hormone (TSH) and Prolactin (PRL) in rotifers. Analyses included the avidin-biotin-peroxidase complex method with primary antibodies LH (Anti-Rat LH serum for RIA), PRL (Anti-Rat PRL serum for RIA), FSH (Anti-Rat FSH serum for RIA) and TSH (Anti-Rat TSH serum for RIA). These hormones were found in females, males and parthenogenetic and sexual eggs of the freshwater Brachionus calyciflorus. The immunoreactivity of FSH, LH, TSH and PRL in females was observed in: ovaries, cerebrum, mastax, stomach, lorica, and the stomach gland. However, in males LH was observed only at the trochal disk and cerebrum. The hormones FSH, TSH and PRL, were observed in testicles, contractil vesicles, and cementary gland of males. Regarding amictic or parthenogenetic eggs, the hormones LH, FSH, TSH, and PRL were located mainly in the micromeres, and the staining in the macromeres was weak. On the other hand, in the mictic or sexual eggs the inner shell is stained for the hormones PRL and LH, opposite to the staining of FSH and TSH, located mainly in the embryo. In general, immuno-reactivity was observed in areas important for the reproductive, excretory, digestive and developmental processes. Rev. Biol. Trop. 57 (4): 1049-1058. Epub 2009 December 01. Se logró detectar la presencia de las hormonas: Hormona Luteinizante (LH), Hormona Folículo Estimulante (FSH), Hormona Estimulante de la Tiroides (TSH) y Prolactina (PRL) en Brachionus calyciflorus siendo el primer reporte de la presencia de dichas hormonas en rotíferos. Estas hormonas fueron identificadas por un método inmunológico-histológico-químico usando el complejo avidina-biotina- peroxidasa con los siguientes anticuerpos primarios: LH (Anti-Rata LH suero para RIA), PRL (Anti-Rata PRL suero para RIA), FSH (Anti-Rata FSH suero para RIA) y TSH (Anti-Rata TSH en suero para RIA). Estas hormonas se encontraron en las hembras, machos, huevos partenogenéticos y huevos sexuales del rotífero dulceacuícola B. calyciflorus. La reactividad inmunológica de FSH, LH, PRL y TSH en las hembras se observó en ovarios, cerebro, mástax, estómago, lorica, y la glándula del estómago. Sin embargo, en machos, la LH se observó sólo en el disco trocal y cerebro mientras que las hormonas FSH, PRL y TSH, se observaron en testículos, vesícula contráctil, y la glándula cementaria. En cuanto a los huevos partenogenéticos o amícticos, las hormonas LH, FSH, TSH, y PRL, se encontraron principalmente en los micrómeros, y en los macrómeros la tinción es débil. Por otra parte, el huevo sexual o míctico muestra reactividad inmunológica en la cubierta interior del huevo para las hormonas LH y PRL, lo contrario para FSH y TSH, las cuales se observaron principalmente en el embrión. La reactividad inmunológica fue observada, en general, en áreas importantes para los procesos reproductivos, excretorios, digestivos y del desarrollo.